Gelatinase (MMP-2 and -9) expression profiles during gestation in the bovine endometrium - Sato Takashi; Todoroki Junichi; Yamada Osamu; Takahashi Toru; Ushizawa Koichi; Kizaki Keiichiro; Ito Akira; Hashizume Kazuyoshi (BMC, 2008)
Abstract Background Various molecules participate in implantation and maintaining endometrial function during gestation. The remodeling of endometrial matrices is a necessary process in the coordination of gestational progress. Matrix-metalloproteinases (MMPs) like gelatinases (MMP-2 and -9) and collagenase (MMP-1) are considered to play important roles in this process. We examined MMP-2 and -9 expression using zymography, in situ hybridization, real-time PCR, and microarray analysis to clarify their roles in the bovine endometrium during gestation. Methods Endometria, placentomes, and fetal membranes were collected from Japanese black cows that were killed on day 15 to 252 of gestation or during their estrous cycle. The gene expression of MMP-related molecules (mainly MMP-2 and -9) was examined using a custom-made microarray, real-time RT-PCR, and in-situ hybridization. Gelatinase activity was detected by zymography and film in situ zymography. Results Both gelatinases were expressed in the endometrium and fetal tissues throughout gestation. MMP-2 gene expression declined with the progress of gestation, but its intensity was maintained at a high level during the peri-implantation period and increased in late gestation. The expression level of MMP-9 was stably maintained, but was relatively low compared to that of MMP-2. These gene expression patterns matched those detected by zymography for the proteins. Microarray analysis suggested that the functions of MMP-2 during implantation and the last part of gestation are closely related with those of other molecules such as tissue inhibitors of metalloproteinase (TIMP)-2, a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) 1, membrane type 1 (MT1)-MMP, and extracellular matrix metalloproteinase inducer (EMMPRIN). Conclusion We detected MMP-2 and -9 gene expression in the bovine endometrium and placentome throughout gestation. These data suggest that MMP-2 is one of the main endometrial remodeling factors for implantation and pre-partum in cattle. In cows, as is the case in humans and rodents, gelatinases participate in endometrial remodeling, and their activities depend on the balance of activators and inhibitors; i.e., TIMP, MT-MMP, EMMPRIN, MMP-2, MMP-9, and so on.